Growth of Three Varieties of Kenaf (Hibiscus cannabinus L.) by Giving N, P, K Fertilizer Under Rubber Produce Area - Sitindaon, Putri; Hanum, Chairani; Ginting, Jonis (Jurnal Agroekoteknologi, 2017)
The objective of this research was to study three varieties kenaf effect growth by giving N,P,K fertilizer were plant under the rubber produce. The experiment was conducted in PT. Perkebunan Nusantara III Silau Dunia Village District of Serdang Bedagai, from September 2015 to January 2016. The method used was factorial randomized block design with 2 factor, the first factor was varieties i.e. KR 9, KR12 and KR14, the second factor was N,P,K fertilizer i.e.  (0 g/plant hole: 1,80 Urea ; 0,60 g TSP ; 0,60 g KCl / plant hole: 3,60 g Urea ; 1,20 g TSP ; 1,20 g KCl / plant hole: 5,40 g Urea ; 1,80 g TSP ; 1,80 g KCl /plant hole). The result showed that three varieties of kenaf by giving N,P,K fertilizer under rubber shelter and interaction between them has not significantly affected to all parameters observed I.e. plant height, number of leaves, shoot fresh weight, and shoot dry weight at 4-13 WAP.